REVIEW OF WπGR CLOSED SETS IN TOPOLOGICAL SPACES - S. R, SREENA; E. N, DR. SATHEESH; MATHEW, DR.VARUGHESE (JOURNAL OF ADVANCES IN MATHEMATICS, 2024)
In this paper we introduce a new class of sets called weakly π generalized regular closed (wπgr closed) sets. A subset A of X is called wπgr closed set if cl( int A) ⊆U whenever A⊆U and U is πgr open in X. The complement of wπgr-closed set is called wπgr-open set in X. We denote the family of all wπgr closed sets in X by wπGRC(X) and wπgr open sets in X by wπGRO(X))